Pengaruh Nilai Uji Tarik Terhadap Kuat Impak pada Komposit Serat Daun Nanas - Hutauruk, Siti Aulia; Jumiati, Ety; Daulay, Abdul Halim (Fakultas Teknik UMSU, 2024)
Research has been conducted to determine the effect of tensile test values on impact strength. Using an experimental method and a quantitative approach, the variations in the composition of pineapple leaf fiber with polyester resin adhesive are as follows: sample A (40%:60%), sample B (45%:55%), sample C (50%:50%), and sample D (55%:45%). The molding process used a hot press with a pressure of 0.1 MPa and a temperature of 150°C for 15 minutes. The preparation and testing of specimens referred to ASTM D638-03 for tensile testing and ASTM D6110-10 for impact testing. The tensile test results were 24.71 MPa for sample A, 25.97 MPa for sample B, 26.00 MPa for sample C, and 20.73 MPa for sample D. The impact strength results were 0.02779 J/mm² for sample A, 0.02997 J/mm² for sample B, 0.03044 J/mm² for sample C, and 0.0306 J/mm² for sample D. The experiment showed that as the tensile test values increased, there was an effect on the impact strength results..